Understanding and Combating Resistance to Online Learning. (December 2016) - Vivolo, John
Resistance to change is an easy thing for human beings to understand. It is at the heart of our desire to find comfort with the familiar such as family, friends and our homes. We create homes that are designed a certain way and usually are slow to change. We make friends for years and keep those memories etched in stone, even though time and age create a romanticised version of the past. Change scares us so much that we reflect on our past, the old days, with such reverence that we paint over the ugly parts. However, we still talk about how change is good. Consider our institutionalised method of learning that has existed for centuries and involved people sitting learning from another person in a physical space. Then, suddenly in the last 20 years, there is a complete change and almost every major institution in the United States and many around the world decided to offer a new method of learning. Enter online learning. It becomes a sudden disruption to a traditional system. It is not surprising that there has been resistance from faculty, students and administrators. Even in the face of evidence that online learning works as effectively as traditional onsite learning, still people resist. Oddly enough, the resistance can come from those who base their careers on facts and research, but continue to ignore the evidence. Even performance results get ignored. While this article will address the source of resistance to online learning, it will focus primarily on how to combat this resistance within an organisation or institution.